Comparative Analysis of Tear Film Parameters in Patients Undergoing Pterygium Excision by Conjunctival Autograft or Bare Sclera Technique Augmented by Intraoperative Mitomycin C Application - Neeraj Sharma; Sonakshi Sehrawat; Saumya Sharma (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Excision of the pterygium has been shown to enhance tear film stability. The study was designed to assess the effects of pterygium removal utilising two different surgical procedures on tear film parameters: bare sclera with Mitomycin C (MMC) and conjunctival autograft. The bare sclera with MMC application and conjunctival autograft techniques are the two most common treatments for pterygium. Conjunctival autograft is a procedure in which the superior conjunctiva of the patient’s eye is removed in one piece and the excised tissue is used to cover the area where the pterygium was removed. The bare sclera with MMC application procedure involves removing the pterygium and intraoperatively applying 0.02% MMC to the scleral bed, leaving it to re-epithelialise. Aim: To analyse the improvement in tear film parameters of patients undergoing pterygium excision by conjunctival autograft or bare sclera technique augmented by intraoperative MMC application. Materials and Methods: The prospective interventional study was conducted in Department of Ophthalmology, SGT University affiliated hospital, Gurugram, Haryana, India, from January 2019 to January 2020. A total of 54 patients were divided into two groups: Group 1 has 26 patients undergoing pterygium excision with bare sclera technique (with MMC 0.02%), and Group 2 has 28 patients undergoing pterygium excision with conjunctival autograft technique (with MMC). Tear Break-up Time (TBUT) and Schirmer’s I were measured in 54 eyes with pterygium before and after surgery. Data analysis was done using two tail (inequality) test on Statistical Package for the Social Sciences (SPSS) software version 28.0. Patients were randomly divided into two groups by using RAND between software. Results: The mean preoperative Schirmer’s I was 9.333 mm which improved to 12.203 mm after pterygium excision, which was a statistically significant change irrespective of the technique used. The mean preoperative Tear Break-up Time (TBUT) was 7.212 seconds which improved to 13.059 seconds after pterygium excision, which was a statistically significant change irrespective of the technique used. In the autograft group, TBUT improved from preoperative mean value of 7.253 seconds to 14.0 seconds and Schirmer’s I mean values improved from 9.178 mm to 12.678 mm, respectively. In the bare sclera group, TBUT improved from preoperative mean value of 7.169 second to 12.046 second and Schirmer’s I mean values improved from 9.500 mm to 11.692 mm, respectively. The mean postoperative Schirmer’s I in autograft technique was 12.678 mm and postoperative Schirmer’s I in bare sclera technique was 11.692 mm. The postoperative improvement in both groups was statistically similar. The mean postoperative TBUT in autograft technique was 14 seconds and postoperative TBUT in bare sclera technique was 12.046 seconds. Postoperative results in the autograft group were statistically better than the bare sclera group. Conclusion: The tear film stability parameters in pterygium patients improved after surgery in both the groups. Statistical analysis of postoperative Schirmer’s I data was similar in both the techniques. Although postoperative TBUT values were statistically better in the autograft group, the mean value in both the techniques were more than ten seconds. The analysis of data indicates that bare sclera technique with MMC can be used as an alternative surgical procedure in patients with scarred conjunctiva or in situations where superior conjunctiva has to be preserved for future use.